The Economic Crisis and Public Health - Barry S. Levy; Victor W. Sidel (Social Medicine Publication Group, 2009)
The current global economic crisis seriously threatens the health of the public. Challenges include increases in malnutrition; homelessness and inadequate housing; unemployment; substance abuse, depression, and other mental health problems; mortality; child health problems; violence; environmental and occupational health problems; and social injustice and violation of human rights; as well as decreased availability, accessibility, and affordability of quality medical and dental care. Health professionals can respond by promoting surveillance and documentation of human needs, reassessing public health priorities, educating the public and policymakers about health problems worsened by the economic crisis, advocating for sound policies and programs to address these problems, and directly providing necessary programs and services.